Analisis Financial Distress Untuk Memprediksi Potensi Kebangkrutan PT. X Yang Terdaftar Di BEI - Saladin, Hendry; Oktariansyah, Oktariansyah; Sari, Novita (E-Jurnal Akuntansi, 2022)
Financial distress can occur in every company. If financial distress is not immediately addressed, it can lead to bankruptcy. This study aims to determine the potential for bankruptcy at PT. X is listed on the Indonesia Stock Exchange (IDX) using the Springate model, the Zmijewski model and the Grover model. The method used is a qualitative method. The research sample is a statement of financial position and profit and loss of PT. X the first quarter of 2021 - the first quarter of 2022. The results of the research from the three models used are only the Springate model which predicts the company in a potentially bankrupt condition, while the Zmijewski model and the Grover model predict the company in a non-bankrupt potential condition. Keywords: Financial Distress; Springate Model; Zmijewski Model; Grover Model